Influence of reverberation field conditions on sound power evaluation with the aid of intensity method - CIEŚLIK, J.; PANUSZKA, R. (Archives of Acoustics, 1993)
The results of investigations presented in the article were aimed at explaining how the conditions of acoustic field described by the room absorption and reverberation time can influence the calculated sound power value determined by the sound intensity measurements. As the sound source the rigid piston in the large baffle was used. The measurements of sound intensity and sound pressure were done in the free field and diffuse field conditions. The total absorption of the room was changed.